Withdrawal from sport training of young talented basketball players and its impact on selection in sport - Litkowycz, Ryszard; Olex-Zarychta, Dorota; Grygorowicz, Monika; Dzienisiewicz, Izabela (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The effectiveness of a sport training program is determined by its adjustment to the expectations and abilities of each player. However, only 20 to 25% of players maintain their sport level after advancing from the junior to the senior category, and many of them simply give up sport training. Aim of Study. The aim of the study was to evaluate the scope of the phenomenon of withdrawal in young basketball players and to determine the reasons why gifted teens discontinue training basketball. Material and Methods. The research focused on basketball players born between 1984 and 1989, who participated in the Silesian Macroregion Team training programs in the years 1999-2003. 54 players were examined in the study (40 males, 14 females) by way of questionnaires filled in by their basketball coaches. Results. The obtained data obtained shows that currently only 7 subjects continue to play basketball (3rd, 2nd or 1st division), and the remaining 47 subjects discontinued basketball training completely. The reasons forgiving up training basketball indicated by the coaches included lack of motivation, lack of possibilities to continue training in a senior category, and injuries. At the same time the coaches evaluated the physical and mental potential of these players including diligence, on-court intelligence, physical fitness, motor skills, and sufficient mastery of technique to continue training. Conclusions. Coaches should pay more attention not only to players’ skills and fitness, but also to their passion, motivation for training and physical efforts crucial each player’s decisions to continue the training
Keywords: basketball; predispositions; selection; young talents; withdrawal